Curative effect of glycyrrhetinicacid for diabetic nephropathy animal model - LI Xiao-qin; SHEN Yin; SHI Jun (Linchuang shenzangbing zazhi)
Objective To study the effect of glycyrrhetinicacid on the diabetic nephropathy(DN) animal model. Methods In order to estimate the effect of glycyrrhetinicacid treatment on the blood glucose,body weight,urine creatinine,the ratio of urinary protein/creatinine,the sedimentation of extracellular matrix and the apoptosis of kidney cells,we built the animal models of type one and type two DN. Type one mouse model of DN included control group,control group plus glycyrrhetinicacid, DN group and DN group plus glycyrrhetinicacid. Type two DN model included control group,DN group and treatment group. Results Compared with the control group,the level of blood glucose and the ratio of urinary protein/creatinine were significantly increased in DN group and the difference was statistically significant(P < 0. 0 1). The deposition of extracellular matrix and the apoptosis of kidney cells increased,whereas the level of urina creatinine decreased in DN group as compared with control group and the difference was statistically significant(P < 0. 0 1). As compared with DN group,the level of urine creatinine and the ratio of urinary protein/creatinine in DN plus glycyrrhetinicacid group were significantly different(P < 0. 0 1),the sedimentation of extracellular matrix obviously relieved and the apoptosis of kidney cells decreased. In type one DN model,there was significant difference in body mass between Control group and DN group(P < 0. 0 5) and at the same time,there was significant difference in body mass between DN group and DN plus glycyrrhetinicacid group(P < 0. 0 1). Conclusions The treatment of GA could protect against the renal lesions of type one and type two DN animal model,thereby delaying the progress of the kidney diseases.